Does the shape of a cup influence coffee taste expectations? A cross-cultural, online study. (March 2017) - Van Doorn, George; Woods, Andy; Levitan, Carmel A.; Wan, Xiaoang; Velasco, Carlos; Bernal-Torres, Cesar; Spence, Charles
Highlights: Shape-taste expectations elicited by pictures of mugs were examined. The relevant research about crossmodal associations is highlighted and reviewed. The width and height of the mugs was shown to be important. Findings highlight the complex nature of shape-flavour interactions. Abstract: We report a study designed to investigate whether shape-taste crossmodal correspondences would influence consumers' expectations concerning coffee. To that end, we conducted a cross-cultural online survey with respondents (N = 309) from China, Colombia, and the United Kingdom (UK). The participants had to rate eight coffee mugs on eight scales by arranging the mugs within a 1000 × 250 pixel box, placing each mug so that its horizontal position matched how strongly they thought the mug matched the scale presented. Amongst other findings, the results revealed that (1) the coffee was expected to be more aromatic from narrower diameter mugs, (2) the coffee associated with shorter mugs was expected to be both more bitter and more intense, and (3) the coffee was expected to be sweeter from wider diameter mugs. An interesting cross-cultural finding was that participants from the UK expected the mugs to be hotter than participants from either China or Colombia. These results add to a large and growing body of research highlighting the associations between visual information and a product's likely (or expected) sensory qualities. These findings may be useful to those preparing coffee as they suggest that coffee should be presented in certain mugs in order to convey a message that is congruent with the consumer's expectations.